Strategi Pembangunan Pariwisata Desa Berbasis Ekonomi Kreatif - Dahlan, Mubarak (Jurnal Ekonomi dan Riset Pembangunan, 2024)
This study aims to determine the forms of creative economy-based tourism sector development strategies, especially in rural areas in Indonesia. This research is descriptive qualitative where the data analysis used is data reduction, data presentation, and conclusion drawing. The results showed: (1) There is still a lack of maximum development of the tourism sector in rural areas with a creative economy orientation, partly due to the lack of awareness and participation of local communities (2) The government needs to conduct intensive socialization and continuous guidance through various programs supported by adequate funding, and (3) The strategy of creative economy-based tourism development in rural areas must involve outside parties as support for the implementation of the program.